Gaya Komunikasi pada Live Shopping Produk Kecantikan di TikTok: Perspektif Komunikasi Islam - Nurrochmah, Erva Uyun Nurrochmah (Journal of Islamic Communication Studies, 2025)
The social commerce phenomenon on TikTok transforms shopping activities into shoppertainment, where persuasion is delivered through signs working emotionally and culturally. This research has a dual objective: 1) to uncover the construction of meaning and contemporary myths in beauty product TikTok Live through Roland Barthes’ semiotic analysis, and 2) to analyze the ethical implications of the communication style from the Islamic Communication Perspective. The method utilized is qualitative descriptive with media text analysis, focusing on TikTok Live broadcasts by Skintific Indonesia. The sign analysis results show that the host utilizes popular diction (“racun,” “gercep,” “checkout now”) combined with enthusiastic intonation, gestures, and visual timers to build urgency and a parasocial bond. Semiotically, these signs successfully naturalize two main myths: “Instant Beauty” and “Smart Shopper is the Quick Buyer.” Normatively, the study concludes that the Instant Beauty Myth potentially violates the principle of Qaulan Sadida and the prohibition of Ghurur (deception) due to creating unrealistic expectations. Meanwhile, the Smart Shopper Myth promotes Israf (excessive consumption), contradicting the principle of tawazun (balance). This study asserts that TikTok live shopping serves as a cultural mechanism that generates ethical tension within the context of digital muamalah, demanding adherence to values of honesty and moderation.